PENGARUH RASIO KESEHATAN BANK TERHADAP KINERJA KEUANGAN BANK SYARIAH PERIODE 2010-2013 - Iwan Fakhruddin; Tri Purwanti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
The research was aimed to analyze the effect of risk base bank ratio to the financial performance of syariah bank listed in Central Bank of Indonesia. The population covered all syariah Bank and the sample was 11 syariah Bank. Then, the data analyze through double regression. The research showed that Capital Adequacy Ratio (CAR), Non Performing Ratio (NPF), Operational efficiency Ratio (OER), Financing to Deposit Ratio (FDR), Quality of Productive Active (KAP) effected simultaneously to Return of Asset (ROA). CAR variable had positive and significant effects to ROA. NPF contributed negative and significant effects to ROA. OER comprised negative and significant effect to ROA. FDR had positive and significant effect to ROA. KAP got negative and significant effect to ROA.Keywords : CAR, NPF, OER, FDR, KAP, and ROA.